Spine phenotypes - Samartzis, Dino; Karppinen, Jaro Ilari; Williams, Frances Mary Kingsley (Academic Press, 2022)
"The era of big data and personalized spine care has arrived. Within that, imaging and clinical phenotypes are key in establishing personalized algorithms for patient care. This is particularly important in developing novel diagnostics and therapeutics as well as predicting outcomes and establishing preventative measures for various spinal disorders. Spine Phenotypes is a comprehensive resource that outlines phenotype descriptions, their imaging measurements and classifications, and provides an in-depth discussion regarding spine pathology and its clinical relevance."--Provided by publisher.